2009
DOI: 10.1124/mol.108.052423
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Scanning Mutagenesis of the Second Extracellular Loop of Type 1 Corticotropin-Releasing Factor Receptor Revealed Residues Critical for Peptide Binding

Abstract: Upon binding of the corticotropin-releasing factor (CRF) analog sauvagine to the type 1 CRF receptor (CRF 1 ), the amino-terminal portion of the peptide has been shown to lie near Lys257 in the receptor's second extracellular loop (EL2). To test the hypothesis that EL2 residues play a role in the binding of sauvagine to CRF 1 we carried out an alanine-scanning mutagenesis study to determine the functional role of EL2 residues (Leu251 to Val266). Only the W259A, F260A, and W259A/F260A mutations reduced the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 44 publications
1
47
0
4
Order By: Relevance
“…3C). Astressin is a CRF peptide antagonist that is less sensitive to receptor activation-associated conformational changes than agonists, and it interacts with the extracellular N-domain of CRF 1 R (8,15 (Fig. 4A), in a manner similar to the effect of the MTSEA reaction that adds a Lys-like side chain to F203…”
Section: Use Of the Substituted Cysteine Accessibility Methods (Scam) mentioning
confidence: 99%
See 3 more Smart Citations
“…3C). Astressin is a CRF peptide antagonist that is less sensitive to receptor activation-associated conformational changes than agonists, and it interacts with the extracellular N-domain of CRF 1 R (8,15 (Fig. 4A), in a manner similar to the effect of the MTSEA reaction that adds a Lys-like side chain to F203…”
Section: Use Of the Substituted Cysteine Accessibility Methods (Scam) mentioning
confidence: 99%
“…After 1-5 days, frozen lysates were thawed and centrifuged at 1800 ϫ g for 10 min at 4°C, and the supernatants were neutralized with 2 N NaOH. Quantification of cAMP in the neutralized supernatants was performed using a competitive binding assay as described previously (15). In brief, supernatants were transferred to polypropylene mini-tubes (20 l/tube) containing buffer A (100 mM Tris-HCl, pH 7.4, 100 mM NaCl, and 5 mM EDTA) with 1-1.5 nM [2,8-3 H]cAMP (PerkinElmer Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…94,95 The latter finding is in agreement with the results of an alanine mutagenesis study, which has suggested that Trp259 and Phe260 in the EL2 of CRF1 receptor most likely interact with ligands, and specifically with the amino-terminal residues 8-10 of SVG and the corresponding ones of CRF. 96 Furthermore, this study has proposed that the interaction between the amino-terminal region of CRF family peptides and Trp259 and Phe260 of CRF1 seems to be critical for receptor activation and the subsequent appearance of a biological effect. 96 In addition to EL2, the first extracellular loop (EL1) of CRF1 has been demonstrated as playing a part in peptide binding, given that the amino-terminally located residues 17 and 22 of UCN analogs have been shown in a recent study to be located in close proximity to residues Trp170-Glu179 in the EL1 of CRF1.…”
Section: Crf Receptorsmentioning
confidence: 99%